2021
DOI: 10.3390/cimb43030113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bioavailability after In Vitro Digestion and First Pass Metabolism of Bioactive Peptides from Collagen Hydrolysates

Abstract: Collagen hydrolysates (CHs) are composed of bioactive peptides (BAPs), which possess health enhancing properties. There is a knowledge gap regarding the bioavailability of these BAPs that involves intestinal transport and hepatic first pass effects. A simulated gastrointestinal model was used to generate digesta from two CHs (CH-GL and CH-OPT), which were applied to a novel transwell co-culture of human intestinal epithelium cell line-6 (HIEC-6) and hepatic (HepG2) cells to simulate in vivo conditions of absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The concurrent analysis of the free AA content, as they may also contribute to CH bioactivity, was determined using LC-MS equipped with a hydrophilic interaction chromatography (HILIC)-Z column. Digestion efficiency and the release of different peptide sequences are a direct result of differing CH preparation or purification methods to ensure that CHs are more digestible and can impact peptide profile, bioavailability, and downstream bioactivity [ 77 , 90 , 91 ].…”
Section: Digestion and Bioavailability Of Chs And Ch-derived Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The concurrent analysis of the free AA content, as they may also contribute to CH bioactivity, was determined using LC-MS equipped with a hydrophilic interaction chromatography (HILIC)-Z column. Digestion efficiency and the release of different peptide sequences are a direct result of differing CH preparation or purification methods to ensure that CHs are more digestible and can impact peptide profile, bioavailability, and downstream bioactivity [ 77 , 90 , 91 ].…”
Section: Digestion and Bioavailability Of Chs And Ch-derived Peptidesmentioning
confidence: 99%
“…The human colonic adenocarcinoma cell line, Caco-2, has frequently been used to assess the SI absorption of drugs, nutrients, and dietary components, as well as CH and CH-derived peptides [ 76 , 91 , 98 , 99 , 100 ]. The bioavailability of CH peptides typically depended on the hydrolysis method used to generate the CHs [ 90 ].…”
Section: Digestion and Bioavailability Of Chs And Ch-derived Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cucumber peptides (SCPs) obtained from A. leucoprocta by protease hydrolysis, and isolated and purified by neutral proteinase complex are small molecule peptides ( 9 ). The study of the bioavailability of bioactive peptides after in vitro digestion and first metabolism revealed that all peptides were transported across the intestinal cell layer to varying degrees, and are not metabolized by the liver ( 10 ). It has also been shown that the diversity of peptides increases after in vitro gastric and small intestinal digestion ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolyzed collagen, as a source of specific amino acids, can perform a building function and be a material for the formation of new collagen fibrils in the connective tissues of cartilage, thereby restoring them after damage [7]. Short collagen-derived peptides consisting of two or three amino acids are easily absorbed in the intestine [8]. If the collagen-derived peptides are consumed, the process of protein digestion in the gastrointestinal tract is facilitated [9], and the level of amino acids entering the cartilage increases; those amino acids are used further in collagen biosynthesis in chondrocytes [10].…”
Section: Introductionmentioning
confidence: 99%